PENGETAHUAN KEPALA SEKOLAH TENTANG SUPERVISI PENDIDIKAN DI TK SE- KECAMATAN TAMPAN KOTA PEKANBARU - Nurzubaini Nurzubaini; Zulkifli Zulkifli; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this research is to determine the level of knowledge the headmaster about the supervision education kindergarten in the District Tampan Pekanbaru city.Population and sample in this research is all kindergarten headmaster of 48 people as sub district Pekanbaru. The techniques data collection that use the test in the form of multiple choice questions.The data analysis using the percentage formula. Based on the result obtained on the level of knowledge of the headmaster supervision education kindergarten Tampansub district Pekanbaru in middle category was 85.41% as many as 41people,which is at a height of only category was 6,25% as many as 3 people and that is the lower category was 8.33% as many as 4 people. Based on the analysis of the level of education of the head of school, it also affects the education level of knowledge about the headmaster supervision education. It can be seen from the data analysisis based on the calculation of chi square obtained a figure of 67.866 turns.The figure compared with the chi-square value in the table with dk by 8 is at 5% significance level that is equal to 15.507,The calculation result is greater than the chi square chi square results in the table(67.866>15.507).Based on the analysis of the length of employment as principal, it does not affect the working lives of the principal knowledge of educational supervision.It can be seen from the data analysis is based on the calculation of chi square obtained a figure of 22.223 turns.The figure compared with the chi-square value in the table with dk by 22 at the5% significance level that is equal to 33.924, the calculation result is smaller than the chi square chi square results in the table(22.223 <33.294.Keywords: Knowledge of headmaster, Supervision EducationWisuda Oktober